2013
DOI: 10.1016/j.toxlet.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of developmental lead exposure on expression of DNA methyltransferases and methyl cytosine-binding proteins in hippocampus

Abstract: Developmental exposure to lead (Pb) has adverse effects on cognitive functioning and behavior that can persist into adulthood. Exposures that occur during fetal or early life periods may produce changes in brain related to physiological re-programming from an epigenetic influence such as altered DNA methylation status. Since DNA methylation is regulated by DNA methyltransferases and methyl cytosine binding proteins, this study assessed the extent to which developmental Pb exposure might affect expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 45 publications
9
71
0
2
Order By: Relevance
“…In this study, there was a significant increase in Pb levels in patients with ASD compared with the control group, coupled with a correlation between Pb concentration and the severity of SRS and CARS scores. These observations support a recent study on patients with ASD by Schneider et al (2013) [24], who suggested potential epigenetic effects of developmental Pb exposure on DNA methylation. These effects were mediated at least partially through the dysregulation of methyltransferases as multiple forms of proteins, at least some of which are potentially involved in cognition [25], and the resulting abnormalities were recorded in patients with ASD [26].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, there was a significant increase in Pb levels in patients with ASD compared with the control group, coupled with a correlation between Pb concentration and the severity of SRS and CARS scores. These observations support a recent study on patients with ASD by Schneider et al (2013) [24], who suggested potential epigenetic effects of developmental Pb exposure on DNA methylation. These effects were mediated at least partially through the dysregulation of methyltransferases as multiple forms of proteins, at least some of which are potentially involved in cognition [25], and the resulting abnormalities were recorded in patients with ASD [26].…”
Section: Discussionsupporting
confidence: 91%
“…Lead alters the expression of the NMDAR subunits resulting in the defective NMDAR structure affecting the hippocampal development and maturation [35,36,40]. Lead is believed to influence the expression of hippocampal DNA methyltransferases and methyl cytosine-binding proteins which are involved in early brain development process [41]. Lead exposure from the gestation day 0 to the postnatal day 21 in rats, enhances oxidative stress and alters the apoptosis process in developing hippocampal neurons [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aggregation of the amyloid peptide β was particularly enhanced in these monkeys after re-exposure to Pb 2+ . These epigenetic modifications may be due to DNA methylation mediated in part through lead-induced dysregulation of methyltransferases (Schneider et al, 2013). The particular sensitivity of cortical areas to heavy metal exposure together with the increase of amyloid peptide deposition suggest a link between heavy metal exposure and Alzheimer's pathology (Castoldi et al, 2008;.…”
Section: Tissuementioning
confidence: 99%